ChemInform Abstract: Imidazolium Ion Tethered TsDPENs as Efficient Ligands for Iridium Catalyzed Asymmetric Transfer Hydrogenation of α‐Keto Phosphonates in Water. Issue 34 (4th August 2016) - Sun, Mengxia; Campbell, Joann; Kang, Guowei; Wang, Huigang; Ni, Bukuo
Abstract: A water compatible imidazolium ion tethered TsDPEN ligand (ITT) is applied for the title reaction using sodium formate as hydrogen source.